Discriminative Ability of Electrophysiological Tests Such as Nerve Conduction Velocities for The Classification of Malnourished Children from Normal Children - Agarwal, Anju; Agrawal, Nikhil; Sharma, Neetu; Shukla, Durgesh; Singh Rajput, Ajit (National Journal of Community Medicine, 2023)
Background: Nerve Conduction Velocities (NCVs) measures electrical changes and speed in the nerve. Objectives of this study were: to compare mean velocities, to find rank of importance of different velocities and to frame equation to classify severely acute malnourished (SAM) children with normal children. Material & Methods: Present case- control study was conducted on 50 SAM children and 50 normal children aged 6 months to 59 months. Independent t test and Discriminant analysis was performed. Standardized discriminant coefficient, canonical correlation and Wilks’ Lambda was calculated and p value was judges at 5% level of significance. Results: NCVs were observed significantly lower among the cases as compared with the controls. Sural Sensory Nerve Velocity holds first position followed by Sensory Nerve Velocity. So, in final discriminant model 3 variables i.e., Sural Sensory Nerve Velocity; Median Sensory Nerve Velocity; Tibial Motor Nerve Velocity were used and 42.1 % of the total variance in the discriminant scores not explained by differences among the groups by the three-variable model. Model is able to classify 82.5% cases correctly. Conclusion: Sural Sensory Nerve Velocity; Median Sensory Nerve Velocity; Tibial Motor Nerve Velocity were found as most important nerve conduction velocities with a good classification ability.